Education Islamic Parenting dalam Surah Al-Luqman Ayat 12-19: Prespektif Tafsir Al-Muyassar - Fazaa Daffa Al Khirzin (Transformasi Manageria: Journal of Islamic Education Management, 2024)
Islamic education in the family, as reflected in QS. Luqman verses 12-19, describe Luqman's specialty as a figure who is wise and full of wisdom in the task of educating children. This concept provides a valuable foundation for parents in directing and educating their children, with the hope of success and safety, both in this world and the hereafter. This writing aims to analyze the concepts of Islamic education contained in QS. Luqman verses 12-19. The discussion point of this research focuses on the concept of Islamic Parenting education, by examining how Luqman as a father educated his child until his name was immortalized in the QS. Luqman verses 12-19. In this context, the research will review in depth the educational practices implemented by Luqman, as well as their relevance in the context of Islamic education in the family. This research uses a qualitative approach with a library research method. The results of this research found that the education contained in QS. Luqman according to Tafsir Ibnu Katsir includes: (1) an attitude of gratitude towards Allah SWT who has given him privileges in the form of wisdom, (2) monotheistic education, (3) devotion to his parents, (4), good deeds, (5) worship, and (6) have noble character towards others.